Balance, reframe, and overcome: The attitudes, priorities, and perceptions of exercise‐based activities in youth 12–24 months after a sport‐related ACL injury. Issue 1 (16th May 2021) - Truong, Linda K.; Mosewich, Amber D.; Miciak, Maxi; Pajkic, Andrea; Le, Christina Y.; Li, Linda C.; Whittaker, Jackie L.
Abstract: Attitudes, priorities, and perceptions of exercise directly influence exercise behaviors. Despite the benefits of exercise‐based activities for future health, little is known about how youth who experience an ACL injury view exercise‐based activity beyond the immediate recovery period. A qualitative (interpretative description) approach with one‐to‐one semistructured interviews was used to probe the current attitudes, priorities, and perceptions of exercise‐therapy, physical activity, and sport participation with a purposive sample of youth from an ongoing inception cohort study who experienced an ACL tear or reconstruction in the past 12–24 months. Analyses followed an inductive approach guided by an analytic interpretative description process. Reflexive journaling, memoing, and a detailed audit trail promoted data trustworthiness. A patient‐partner was involved throughout. Ten youth (six women, four men), 15–19 years of age, and a median of 20‐months (16–26) from injury were interviewed. Three overarching themes were identified. ' Balancing physical activity and future knee health' highlighted ongoing negotiations between what were perceived to be competing priorities for return‐to‐sport and future knee health. ' Reframing the value of exercise‐therapy and physical activity' reflected the importance of reshaping attitudes toward exercise as positive and was linked to exercise adherence. 'Overcoming unforeseen exercise challenges ' encompassed persisting psychological and physical challenges perceived to limit exercise‐based activities. Clinical significance: reframing exercise‐based activities in a positive light and leveraging motivation for return‐to‐sport and life‐long knee health may be important strategies for encouraging ongoing exercise therapy and physical activity following a youth ACL injury.